Pavement coating with CO2 adsorption capacity and preparation method thereof

By using polyethyleneimine/gas phase silica/activated carbon composite materials, combined with the two mechanisms of physical adsorption and chemical adsorption, the problems of low adsorption amount and unstable adsorption of existing CO2 adsorbents are solved, and efficient CO2 capture and storage are achieved.

CN119875466APending Publication Date: 2025-04-25HANDAN GUANGTAI HIGHWAY ENG CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411982046.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The adsorption amount of existing CO2 adsorbents is low, especially physical adsorption, which leads to the easy desorption of CO2 after adsorption and cannot effectively reduce CO2 emissions.

Method used

Polyethyleneimine/gas phase silica/activated carbon composite materials are used, combining two mechanisms of physical adsorption and chemical adsorption to enhance the adsorption and removal of CO2.

Benefits of technology

It improves the adsorption capacity of CO2 and the stability of the adsorption process, reduces the desorption phenomenon of CO2, and achieves more efficient CO2 capture and storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure HDA0005221765800000011
    Figure HDA0005221765800000011
Patent Text Reader

Abstract

The invention relates to the technical field of road engineering materials, in particular to a pavement coating with CO2 adsorption capacity and a preparation method thereof. According to the specific technical scheme, the pavement coating with the CO2 adsorption capacity is prepared from components in parts by weight as follows: 8-9 parts of absolute ethyl alcohol, 8-9 parts of polyethyleneimine, 2.5-3 parts of fumed silica, 15-20 parts of epoxy resin, 2.5-3 parts of activated carbon, 7-8 parts of an epoxy resin diluent, 1-1.5 parts of a defoaming agent, 5-6 parts of a silane coupling agent, 5-6 parts of a coalescing agent texanol and 7-8 parts of an epoxy resin curing agent. According to the prepared pavement coating, two CO2 adsorption modes of physical adsorption and chemical adsorption are comprehensively utilized, the requirement of road engineering for high-performance materials is met, the challenges of global emission reduction and sustainable development are actively responded, and a new environment-friendly solution is provided for the field of road engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of road engineering materials, in particular to a road engineering material having CO 2 Adsorptive pavement coating and method for preparing the same. Background Art

[0002] With the acceleration of industrialization and modernization, global greenhouse gas emissions continue to increase, including carbon dioxide (CO 2 ) is one of the most important greenhouse gases. 2 Excessive emissions of CO2 have led to global warming and frequent extreme climate events, posing a serious threat to human society and natural ecosystems. 2 Reducing emissions and enhancing carbon sink capacity have become urgent tasks in global environmental governance.

[0003] Transportation is one of the main sources of global carbon emissions. As the number of motor vehicles in the world continues to grow, this proportion is expected to continue to rise. Therefore, emission reduction in the transportation sector is crucial to achieving global climate goals. The realization of the "dual carbon" goal requires profound changes and innovations in many fields such as energy structure, industrial production, and transportation. As an important part of transportation infrastructure, road engineering not only consumes a lot of energy during its construction and maintenance, but also directly or indirectly generates CO 2 In addition, automobile exhaust emissions during road use are also a major source of urban air pollution and CO 2 Therefore, developing new environmentally friendly pavement materials and improving the environmental performance of roads are of great significance for alleviating environmental pressure and promoting green transformation in the transportation sector.

[0004] With the improvement of environmental awareness and the popularization of the concept of sustainable development, the market demand for environmentally friendly pavement materials is growing. Such materials should not only meet traditional road performance requirements, such as durability and skid resistance, but also have environmentally friendly properties, such as low emissions, high adsorption and recyclability. However, the current CO 2 Adsorbents generally have the problem of low adsorption capacity, especially those based on physical adsorption, so the adsorption of CO 2 There will be desorption afterwards. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a CO 2 The pavement coating with high adsorption capacity and its preparation method comprehensively utilize physical adsorption and chemical adsorption to CO 2 The adsorption method not only meets the demand for high-performance materials in road engineering, but also actively responds to the challenges of global emission reduction and sustainable development, providing a new environmentally friendly solution for the field of road engineering.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0007] The invention discloses a method having CO 2 The absorbent road coating comprises the following components in parts by weight:

[0008] 8-9 parts of anhydrous ethanol, 8-9 parts of polyethylene imine, 2.5-3 parts of fumed silica, 15-20 parts of epoxy resin, 2.5-3 parts of activated carbon, 7-8 parts of epoxy resin diluent, 1-1.5 parts of defoaming agent, 5-6 parts of silane coupling agent, 5-6 parts of film-forming aid alcohol ester dodecahydrate, and 7-8 parts of epoxy resin curing agent.

[0009] Preferably, the silane coupling agent is KH 570, the film-forming aid alcohol ester is 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, the defoaming agent is 1,2-dichloropropylene, and the epoxy resin diluent is n-butyl glycidyl ether.

[0010] Preferably, the purity of the polyethyleneimine is 99%, and the specific surface area of ​​the fumed silica is not less than 120 m 2 / g, purity ≥99%; the activated carbon is 200 mesh.

[0011] Accordingly, a CO 2 A method for preparing a road coating with adsorption capacity comprises the following steps:

[0012] (1) mixing polyethyleneimine and anhydrous ethanol and stirring them uniformly, and adding fumed silica and activated carbon in sequence under stirring, heating the mixture, and cooling it to room temperature to obtain a composite material;

[0013] (2) Mix the epoxy resin and epoxy resin diluent and stir evenly, add the silane coupling agent, stir evenly, add the composite material, film-forming aid alcohol ester twelve and defoamer in sequence, stir evenly, add the epoxy resin curing agent, stir evenly to obtain a CO 2 Adsorbent road coatings.

[0014] Preferably, during the stirring process, the stirring speed is 100-150 r / min and the stirring time is 5-20 min.

[0015] Preferably, the proportion of each component is, by weight: 8-9 parts of anhydrous ethanol, 8-9 parts of polyethyleneimine, 2.5-3 parts of fumed silica, 15-20 parts of epoxy resin, 2.5-3 parts of activated carbon, 7-8 parts of epoxy resin diluent, 1-1.5 parts of defoaming agent, 5-6 parts of silane coupling agent, 5-6 parts of film-forming aid alcohol ester dodecahydrate, and 7-8 parts of epoxy resin curing agent.

[0016] Preferably, the mass ratio of the polyethyleneimine to anhydrous ethanol is 1:1, and the mass ratio of the polyethyleneimine to activated carbon and fumed silica is 1-4:1:1.

[0017] Preferably, the purity of the polyethyleneimine is 99%, and the specific surface area of ​​the fumed silica is not less than 120 m 2 / g, purity ≥99%; the activated carbon is 200 mesh, the silane coupling agent type is KH 570, the film-forming aid alcohol ester is 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, the defoaming agent is 1,2-dichloropropylene, and the epoxy resin diluent is n-butyl glycidyl ether.

[0018] Accordingly, a CO 2 Road coating with CO adsorption capacity or road coating with CO adsorption capacity prepared by the preparation method 2 Method for using road coating with adsorption capacity to convert CO 2 The absorbent road paint is evenly applied on the road surface by roller coating and then cured at room temperature for 6 to 8 hours.

[0019] Preferably, the pavement paint is applied on the pavement to a thickness of 1.5 to 2 mm; after the pavement paint is applied on the pavement, quartz sand is evenly spread and then cured; the mass ratio of the pavement paint to quartz sand is 10:1 to 4.

[0020] The present invention has the following beneficial effects:

[0021] 1. The present invention uses polyethyleneimine / fumed silica / activated carbon composite material as the core to 2 The adsorption effect of the gas is both physical and chemical, which can reduce CO 2 Desorption from the activated carbon surface improves the stability and long-term effectiveness of the adsorption process and has excellent weather resistance.

[0022] 2. The composite material of fumed silica, activated carbon and polyethyleneimine in the present invention can exert a synergistic effect in the adsorption process. The surface of fumed silica can enhance the adsorption capacity of activated carbon and provide a stable support structure; activated carbon provides an efficient physical adsorption platform; the amino group of polyethyleneimine can enhance CO through chemical adsorption. 2The composite material not only has high surface activity and adsorption capacity, but also can adapt to different environmental conditions. The composite material of fumed silica, activated carbon and polyethyleneimine combines the two mechanisms of physical adsorption and chemical adsorption. The physical adsorption provided by fumed silica and activated carbon can quickly capture carbon dioxide, while polyethyleneimine further enhances the adsorption effect through chemical adsorption. The multiple adsorption mechanisms of this composite material enable it to show good CO removal under various temperature and humidity conditions. 2 Adsorption performance.

[0023] 3. The road coating disclosed in the present invention has the synergy of physical adsorption and chemical adsorption: physical adsorption mainly occurs in the mesopores of the material, while chemical adsorption mainly occurs on the surface modified by PEI. The coating makes full use of the high efficiency of activated carbon and polyethyleneimine in carbon dioxide (CO 2 ) adsorption characteristics, and it is worth noting that: CO adsorbed on activated carbon 2 No desorption will occur, thus ensuring the stability and long-term effectiveness of the adsorption process, which not only improves CO 2 The adsorption capacity of the coating is increased, and the secondary release problem after adsorption is avoided, which is of great significance for the realization of sustainable carbon capture and storage technology. In addition, the coating also combines the excellent adhesion and chemical stability of epoxy resin and the coupling performance of silane coupling agent, making it have excellent anti-stripping and water stability. Using quartz sand as anti-skid particles can further improve the anti-skid performance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a graph showing the anti-skid performance of a coating with quartz sand as anti-skid particles. DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art.

[0027] The invention discloses a method having CO 2 The absorbent road coating comprises the following components in parts by weight:

[0028] 8-9 parts of anhydrous ethanol, 8-9 parts of polyethylene imine, 2.5-3 parts of fumed silica, 15-20 parts of epoxy resin, 2.5-3 parts of activated carbon, 7-8 parts of epoxy resin diluent, 1-1.5 parts of defoaming agent, 5-6 parts of silane coupling agent, 5-6 parts of film-forming aid alcohol ester dodecahydrate, and 7-8 parts of epoxy resin curing agent.

[0029] Among them, the silane coupling agent type is KH 570 (purity ≥ 98%), the film-forming aid alcohol ester is 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate (purity ≥ 95%), the defoamer is 1,2-dichloropropylene (purity GR), and the epoxy resin diluent is n-butyl glycidyl ether. The purity of the polyethyleneimine is 99%, and the specific surface area of ​​the fumed silica is not less than 120m 2 / g, purity ≥99%; the activated carbon is 200 mesh.

[0030] The invention also discloses a method having CO 2 The preparation method of the road coating with adsorption capacity, wherein each component is weighed according to the above ratio, comprises the following steps:

[0031] (1) mixing polyethyleneimine and anhydrous ethanol and stirring them uniformly, and adding fumed silica and activated carbon in sequence under stirring, heating the mixture, and cooling it to room temperature to obtain a composite material;

[0032] (2) Mix the epoxy resin and epoxy resin diluent and stir evenly, add the silane coupling agent, stir evenly, add the composite material, film-forming aid alcohol ester twelve and defoamer in sequence, stir evenly, add the epoxy resin curing agent, stir evenly to obtain a CO 2 The invention discloses a road coating with high adsorption capacity. In each step, the stirring speed is 100-150 r / min and the stirring time is 5-20 min. The mass ratio of polyethyleneimine to anhydrous ethanol is 1:1, and the mass ratio of polyethyleneimine to activated carbon and fumed silica is 1-4:1:1.

[0033] The above has CO 2 A road coating having adsorption capacity or a road coating having CO adsorption capacity prepared by the above preparation method 2 The method of using the road coating with adsorption capacity is to apply the CO 2 The absorbent road paint is evenly applied on the road surface by roller coating and then cured at room temperature for 6 to 8 hours.

[0034] The thickness of the road surface paint applied on the road surface is 1.5 to 2 mm. After the road surface paint is applied on the road surface, quartz sand is evenly spread and then cured. The mass ratio of the road surface paint to quartz sand is 10:1 to 4.

[0035] The present invention will be further described below in conjunction with specific embodiments.

[0036] Example 1

[0037] Preparation of composite materials:

[0038] 1) Place polyethyleneimine and anhydrous ethanol in a clean beaker at a mass ratio of 1:1 and stir with a magnetic stirrer at a speed of 150 r / min for 15 min;

[0039] 2) Add fumed silica to the above solution and stir at a speed of 100 r / min for 20 min;

[0040] 3) Add activated carbon to the above solution and continue stirring at a speed of 100 r / min for 10 min;

[0041] 4) Place the beaker containing the mixture in an oven preheated to 60°C and let it stand for 12 hours to ensure that the anhydrous ethanol is completely evaporated;

[0042] 5) After taking out the beaker and cooling it to room temperature, a polyethyleneimine / fumed silica / activated carbon composite material is finally obtained.

[0043] Example 2

[0044] With CO 2 Preparation of road coatings with adsorption capacity:

[0045] 1) Add epoxy resin and epoxy resin diluent into a beaker according to the corresponding mass parts and stir at a speed of 100 r / min for 10 minutes;

[0046] 2) adding a corresponding amount of silane coupling agent to the mixed solution, and stirring at a speed of 100 r / min for 5 min;

[0047] 3) adding a composite material with a mass ratio of polyethyleneimine: activated carbon: fumed silica = 1:1:1, and then adding a film-forming aid alcohol ester dodecahydrate and a defoamer, and stirring the mixture at a speed of 150 r / min for 15 minutes;

[0048] 4) Finally, add epoxy resin curing agent and stir at a speed of 100r / min for 5 minutes to obtain CO 2 Adsorbent road coatings.

[0049] Comparative Example 1

[0050] This comparative example is the same as all the processes in Example 1, the only difference being that the mass ratio of the composite material polyethyleneimine:activated carbon:fumed silica is 2:1:1.

[0051] Comparative Example 2

[0052] This comparative example is the same as all the processes in Example 2, except that the mass ratio of the composite material polyethyleneimine:activated carbon:fumed silica is 3:1:1.

[0053] Comparative Example 3

[0054] This comparative example is the same as all the processes in Example 2, except that the mass ratio of the composite material polyethyleneimine:activated carbon:fumed silica is 4:1:1.

[0055] Example 3 Carbon fixation performance test of materials

[0056] CO 2 In order to avoid the interference of pollutant gas during the test period, the CO 2 The adsorption device was tested as a blank group, that is, no CO2-coated 2 The blank test was conducted three times, and the test environment was maintained at 20±1℃. The results showed that the gas reaction chamber had good sealing performance. In order to make the indoor experiment more effectively fit the actual road conditions, the CO 2 The concentration was measured on site. 2 The concentration is 640ppm.

[0057] In order to test the CO 2 The coating was applied to the surface of the rutting board (300mm×300mm×50mm) formed indoors by roller coating. After curing for 6 to 8 hours, the initial CO 2 The concentration is 643ppm. In this environment, the CO 2 The adsorption effect was tested and the results are shown in Table 1.

[0058] Table 1CO 2 Adsorption effect test results

[0059] type <![CDATA[Initial CO 2 Concentration (ppm)]]> <![CDATA[CO concentration (ppm) after 120 min]]> 2 ​ <![CDATA[CO 2 Adsorption rate]]> Example 2 643 541 15.9% Comparative Example 1 643 498 22.6% Comparative Example 2 643 447 30.5% Comparative Example 3 643 484 24.7%

[0060] In order to evaluate the carbon fixation effect of the coating, the degradation rate η is used as an evaluation index. The degradation rate formula is shown in formula (1).

[0061]

[0062] Among them, C 1 CO at the start of the experiment 2 The concentration, C 2 CO at the end of the experiment 2 concentration.

[0063] At a 1:1:1 ratio, CO 2 The adsorption rate was 15.9%, which was relatively low. This may be because the content of PEI was not enough to provide sufficient chemical adsorption sites, while AC (activated carbon) and SiO 2 The physical adsorption capacity of PEI was not fully utilized. At the ratio of 2:1:1, the adsorption rate increased to 22.6%, indicating that increasing the proportion of PEI can improve the chemical adsorption capacity, thereby enhancing the overall CO 2 Adsorption efficiency. At a ratio of 3:1:1, the adsorption rate reached the highest, which was 30.5%. This shows that at this ratio, PEI, AC and SiO 2 The synergistic effect between them is the best, the chemical adsorption of PEI and AC / SiO 2 The physical adsorption of AC and SiO2 reached a good balance. At a ratio of 4:1:1, the adsorption rate dropped to 24.7%, which was lower than that of 3:1:1. This may be because too much PEI blocked the AC and SiO2 2 The pores limit the CO 2 The contact area of ​​​​the molecules is reduced, thereby reducing the adsorption efficiency. According to experimental data, PEI, AC and SiO 2 The optimal mass ratio of PEI to AC is 3:1:1, which may be because at this ratio, the chemical adsorption sites provided by PEI are closely related to AC and SiO 2 An optimal balance is achieved between the physical adsorption sites provided.

[0064] Example 4 Road Usability Test of Coating

[0065] 1. Anti-slip performance

[0066] Anti-skid performance is an important indicator that reflects whether the road surface can prevent wheels from slipping and ensure safe driving. Good anti-skid performance can reduce the risk of vehicle slippage and rollover when driving at high speeds, and reduce the probability of traffic accidents. The anti-skid performance of the coating was tested using a pendulum tribometer. A rutting plate without coating and a rutting plate coated with 2mm thick paint were used as controls, and the results are shown in Table 2. The results show that the pendulum friction coefficient value of the original road surface is 63.6, but after coating, the value drops sharply to 48.4, indicating that its anti-skid resistance is insufficient. Considering the importance of anti-skid performance to pavement coatings, improving the anti-skid performance of the coating is crucial to road driving safety.

[0067] Table 2 Test values ​​of coating anti-slip performance

[0068] Test Type Swing value (BPN) Ordinary rutting plate 63.6 Coated rutting plates 48.4

[0069] 2. Water resistance test

[0070] The water resistance of the coating was scientifically evaluated using the immersion test method. The specific experimental steps are as follows: First, the Marshall specimen coated with heat reflective coating is placed in a container with the coating facing down, and deionized water is added to 2 / 3 of the specimen height for immersion. After 24 hours of continuous water immersion treatment, the specimen is removed and the surface moisture is removed using filter paper. Subsequently, the specimen is subjected to a comprehensive visual inspection to record whether there are defects such as discoloration, blistering, peeling, wrinkling, rust or loss of gloss on the coating surface.

[0071] The results showed that after 24 hours of continuous water contact, no fading, blistering or peeling was observed on the coating surface, which confirmed the excellent water resistance of the coating. This result shows that the developed coating has good resistance to moisture and can maintain its physical and chemical stability in a long-term water environment, thus ensuring the long-term durability and functionality of the coating.

[0072] 3. Adhesion test

[0073] The adhesion of the coating was evaluated using the cross-hatch method. The cross-hatch method refers to applying the coating material on the rutting plate specimen, using a tool to divide the coating into a grid shape, and the tool is required to cut the coating to a depth that is required to cut the coating. The number of cuts is 6 times in the horizontal and vertical directions. After the segmentation is completed, the percentage of the area of ​​the local scattered coating blocks that have fallen off the specimen to the entire coating area is counted. According to the size of the shedding percentage, the adhesion index is evaluated. Three repeated experiments were carried out to evaluate the adhesion strength of the coating, and the data obtained have been sorted and presented in Table 3. The results show that the percentage of the shedding area of ​​the coating does not exceed 3%, indicating that the adhesion performance of the coating is good.

[0074] Table 3 Adhesion test results

[0075] Number of tests Shedding area 1 <1% 2 <3% 3 <3%

[0076] Example 5

[0077] In order to enhance the anti-skid performance of the coating, quartz sand (20-40 mesh) was used as anti-skid particles to improve the coating applied to the rutting plate sample. The specific processing flow is as follows:

[0078] 1) 50 g of the coating prepared according to Comparative Example 2 was evenly applied to the surface of the rutting plate sample by a roller coating method to form a uniform coating, ensuring that the coating thickness was 2 mm.

[0079] 2) Spread 5g of quartz sand as anti-skid aggregate evenly on the coating surface, and then let it cure naturally for 6 to 8 hours so that the coating can be completely hardened. After the curing process is completed, the anti-skid performance of the coating is systematically evaluated.

[0080] Comparative Example 4

[0081] This comparative example is the same as all the processes in Example 5, except that 10 g of quartz sand is spread.

[0082] Comparative Example 5

[0083] This comparative example is the same as all the processes in Example 5, except that 15 g of quartz sand is spread.

[0084] Comparative Example 6

[0085] This comparative example is the same as all the processes in Example 5, except that 20 g of quartz sand is spread.

[0086] The measured results are shown in Table 4 and Figure 1 as shown.

[0087] Table 4 Test results of anti-skid performance of quartz sand as enhanced pavement coating

[0088] Test Type Swing value (BPN) Example 5 51.7 Comparative Example 4 56.9 Comparative Example 5 60.8 Comparative Example 6 61.5

[0089] The results show that when the amount of quartz sand added is 5g, the pendulum friction coefficient (BPN) increases to 51.7, and when the quartz sand content increases to 10g and 15g, the BPN value increases significantly to 56.9 and 60.8, respectively, indicating that the introduction of quartz sand has a significant promoting effect on improving the anti-skid performance of the coating. When the quartz sand content is further increased to 20g, the BPN value rises to 61.5, showing further improvement in anti-skid performance, but the gain amplitude slows down, suggesting that after exceeding a certain threshold, the performance improvement effect brought about by the increase in quartz sand content will gradually weaken, that is, it shows the law of diminishing marginal benefits.

[0090] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A road coating with CO2 adsorption capability, characterized in that: In parts by weight, it includes the following components: 8-9 parts of anhydrous ethanol, 8-9 parts of polyethylene imine, 2.5-3 parts of fumed silica, 15-20 parts of epoxy resin, 2.5-3 parts of activated carbon, 7-8 parts of epoxy resin diluent, 1-1.5 parts of defoaming agent, 5-6 parts of silane coupling agent, 5-6 parts of film-forming aid alcohol ester dodecahydrate, and 7-8 parts of epoxy resin curing agent.

2. The road coating with CO2 adsorption capacity according to claim 1, characterized in that: The silane coupling agent type is KH 570, the film-forming aid alcohol ester is 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, the defoaming agent is 1,2-dichloropropylene, and the epoxy resin diluent is n-butyl glycidyl ether.

3. The road coating with CO2 adsorption capacity according to claim 1 or 2, characterized in that: The purity of the polyethyleneimine is 99%, and the specific surface area of ​​the fumed silica is not less than 120 m 2 / g, purity ≥99%; the activated carbon is 200 mesh.

4. A method for preparing a road coating having CO2 adsorption capacity, characterized in that: The following steps are involved: (1) mixing polyethyleneimine and anhydrous ethanol and stirring them uniformly, and adding fumed silica and activated carbon in sequence under stirring, heating the mixture, and cooling it to room temperature to obtain a composite material; (2) The epoxy resin and epoxy resin diluent are mixed and stirred evenly, and a silane coupling agent is added. After stirring evenly, the composite material, the film-forming aid alcohol ester twelve and the defoaming agent are added in sequence. After stirring evenly, the epoxy resin curing agent is added. After stirring evenly, a road coating with CO2 adsorption capacity is obtained.

5. The preparation method according to claim 4, characterized in that: During the stirring process, the stirring speed is 100-150 r / min and the stirring time is 5-20 min.

6. The preparation method according to claim 4, characterized in that: In parts by weight, the distribution ratio of each component is: 8-9 parts of anhydrous ethanol, 8-9 parts of polyethyleneimine, 2.5-3 parts of fumed silica, 15-20 parts of epoxy resin, 2.5-3 parts of activated carbon, 7-8 parts of epoxy resin diluent, 1-1.5 parts of defoaming agent, 5-6 parts of silane coupling agent, 5-6 parts of film-forming aid alcohol ester dodecahydrate, and 7-8 parts of epoxy resin curing agent.

7. The preparation method according to claim 6, characterized in that: The mass ratio of the polyethyleneimine to anhydrous ethanol is 1:1, and the mass ratio of the polyethyleneimine to activated carbon and fumed silica is 1-4:1:

1.

8. The preparation method according to claim 6, characterized in that: The purity of the polyethyleneimine is 99%, and the specific surface area of ​​the fumed silica is not less than 120 m 2 / g, purity ≥99%; the activated carbon is 200 mesh, the silane coupling agent type is KH 570, the film-forming aid alcohol ester is 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, the defoaming agent is 1,2-dichloropropylene, and the epoxy resin diluent is n-butyl glycidyl ether.

9. A method for using the road surface coating with CO2 adsorption capacity according to any one of claims 1 to 3 or the road surface coating with CO2 adsorption capacity prepared by the preparation method according to any one of claims 4 to 8, characterized in that: The road paint with CO2 absorption capacity is evenly applied on the road surface by roller coating, and then cured at room temperature for 6 to 8 hours.

10. The method of use according to claim 9, characterized in that: The thickness of the road surface paint applied on the road surface is 1.5 to 2 mm; After the road surface paint is coated on the road surface, quartz sand is evenly spread and then cured; the mass ratio of the road surface paint to the quartz sand is 10:1-4.

Citation Information

Cited By

  • Pavement coating material with tail gas degradation and CO2 adsorption capacities and preparation method

    CN120519063A

  • Composite coating material for tunnel environment and preparation method thereof

    CN120519064A